Central perception of position sense involves a distributed neural network – Evidence from lesion-behavior analyses. (June 2016) - Findlater, Sonja E.; Desai, Jamsheed A.; Semrau, Jennifer A.; Kenzie, Jeffrey M.; Rorden, Chris; Herter, Troy M.; Scott, Stephen H.; Dukelow, Sean P.
Abstract: It is well established that proprioceptive inputs from the periphery are important for the constant update of arm position for perception and guiding motor action. The degree to which we are consciously aware of the position of our limb depends on the task. Our understanding of the central processing of position sense is rather limited, largely based on findings in animals and individual human case studies. The present study used statistical lesion-behavior analysis and an arm position matching task to investigate position sense in a large sample of subjects after acute stroke. We excluded subjects who performed abnormally on clinical testing or a robotic visually guided reaching task with their matching arm in order to minimize the potential confound of ipsilesional impairment. Our findings revealed that a number of regions are important for processing position sense and include the posterior parietal cortex, the transverse temporal gyrus, and the arcuate fasciculus. Further, our results revealed that position sense has dissociable components – spatial variability, perceived workspace area, and perceived workspace location. Each component is associated with unique neuroanatomical correlates. These findings extend the current understanding of the neural processing of position sense and identify some brain areas that are not classically associated with proprioception.